2019
DOI: 10.1136/bcr-2019-229251
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional and subarachnoid bleeding of a spinal schwannoma presenting with acute cauda equina syndrome

Abstract: We present an unusual case of spinal neurinoma with intralesional and subarachnoid bleeding with acute cauda equina syndrome. A 38-year-old man was admitted to our department after a minor thoracic spinal trauma with right lower limb plegia and urinary retention. MRI showed a T11 intradural tumour with intralesional and subarachnoid haemorrhage. The patient was operated of spinal cord decompression and complete tumour resection. The histological examination documented a schwannoma with large haemorrhagic intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…9 However, our literature review revealed that seven patients (77%) exhibited intracranial clinical symptoms. 8 14 As arterial aneurysm and vascular malformation are the more common causes of SAH, an angiographic study may be the preferential examination to confirm the diagnosis. In our patient, spinal infection or SAH from vascular malformation was considered first.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, our literature review revealed that seven patients (77%) exhibited intracranial clinical symptoms. 8 14 As arterial aneurysm and vascular malformation are the more common causes of SAH, an angiographic study may be the preferential examination to confirm the diagnosis. In our patient, spinal infection or SAH from vascular malformation was considered first.…”
Section: Discussionmentioning
confidence: 99%
“…6 Spinal intradural schwannomas may also result in SAH; however, these are a very rare cause, especially without spinal compression symptoms. In this summary, we identified 8 cases of SAH from a spinal schwannoma reported in the last 20 years [7][8][9][10][11][12][13][14] (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…These hemorrhagic lesions affect almost equally the cervical spine (24%), 4 , 5 , 8 , 11 , 18 , 25 , 27) the lumbar tract (24%), 7 , 13 , 16 , 17 , 21 , 22 , 28) the thoracic tract (20%), 2 , 6 , 9 , 14 , 19 , 29) and the thoraco-lumbar passage (20%) 10 , 12 , 20 , 22 , 24 , 26) while the thoraco-cervical, 15) the sacral-lumbar tract, 30) and the sacral spine 23) are more rarely involved (12%). Bleeding can occur within the tumor (34%), 6 , 11 , 12 , 17 , 22 , 25 , 26 , 27 , 28 , 30) between the inner layer of the dura mater and the arachnoid mater of the meninges (subdural hematoma: 22%) 4 , 5 , 8 , 9 , 16 , 18 , 19) or into the subarachnoid space (subarachnoid hemorrhage: 16%) 7 , 10 , 20 , 21 , 24) ; multiple sites can also be involved (13%), such as intratumoral bleeding with subdural hematoma 2 , 23 , 29) or subarachnoid hemorrhage. 13) …”
Section: Discussionmentioning
confidence: 99%